MODEL OF STUDENTS’WORKBOOK BASED ON DAYAK LOCAL WISDOM FOR SECOND SEMESTER EIGHT YEAR STUDENTS AT SMPN 4 AIR BESAR - Musuwani, Musuwani; Yuliana, Yohanes Gatot Sutapa; Sada, Clarry (ICoTE Proceedings, 2017)
The objective of the study is to develop supplementary reading materials. Based on the observation of the Eight year students in rural area students at SMPN 4 Air Besar , it was found that the problem faced by the students is the ability  reading in English. Students complained that reading text are difficult because the content of the texts are not telling about their background like culture, ritual, tradition and practice. Moreover, the Reading  materials in the existing book used by the school are from java, Bali even from abroad, so it make difficult for students because they donot have the background of the text in their daily live. The method is the research and development with the adaptation of the development proposed Robert Maribe Branch’s framework. To get the data of dayak local wisdom thus identification of needs is done. Data getting from questionnaires, interview and direct observation. The developed materials which consist of six  units contain the custom of dayak local wisdom. The developed materials were then evaluated by three experts. The evaluation showed that besides the good points, there were still a number of weak points. The weak ones were revised according to the feedbacks and suggestions from the experts. The feedbacks from the students  suggested adding some pictures of dayak local wisdom and clear instructions. After some revisions from the feedbacks and suggestions from the expert validation the final product was completed. In conclusion teacher know their students’needs. Thus english language teachers are recommended to write own supplementary material based on students needs (dayak local wisdom if the students are mayority of dayak)